Understanding priorities and needs for child and adolescent mental health in Greece from multiple informants: an open resource dataset. - Koumoula, Anastasia; Marchionatti, Lauro Estivalete; Karagiorga, Vasiliki Eirini; Schafer, Julia Luiza; Simioni, André; Caye, Arthur; Serdari, Aspasia; Kotsis, Konstantinos; Basta, Maria; Athanasopoulou, Lilian; Dafoulis, Vaios; Tatsiopoulou, Paraskevi; et al. (European Child & Adolescent Psychiatry, 2024)
The Child and Adolescent Mental Health Initiative (CAMHI) aims to enhance mental health care capacity for children and adolescents across Greece. Considering the need for evidence-based policy, the program developed an open-resource dataset for researching the field within the country. A comprehensive, mixed-method, community-based research was conducted in 2022/2023 assessing the current state, needs, barriers, and opportunities according to multiple viewpoints. We surveyed geographically distributed samples of 1,756 caregivers, 1,201 children/adolescents, 404 schoolteachers, and 475 health professionals using validated instruments to assess mental health symptoms, mental health needs, literacy and stigma, service use and access, professional practices, training background, and training needs and preferences. Fourteen focus groups were conducted with informants from diverse populations (including underrepresented minorities) to reach an in-depth understanding of those topics. A dataset with quantitative and qualitative findings is now available for researchers, policymakers, and society [https://osf.io/crz6h/ and https://rpubs.com/camhi/sdashboard]. This resource offers valuable data for assessing the needs and priorities for child and adolescent mental health care in Greece. It is now freely available to consult, and is expected to inform upcoming research and evidence-based professional training. This initiative may inspire similar ones in other countries, informing methodological strategies for researching mental health needs.